PENGHAYATAN NILAI-NILAI PANCASILA MELALUI PROFIL PELAJAR PANCASILA PADA PEMBELAJARAN ABAD 21 - Willi Maira; Uswatun Hasanah Yusid; Suci Muharani; Vivi Elida Novita; Vivi Febiyanti (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2024)
This research aims to describe and obtain information regarding the appreciation of Pancasila as an entity and identity of the Indonesian nation through the Pancasila Student Profile in 21st Century Learning. This research uses a qualitative approach using library research methods or literature studies (Library Research). Pancasila has two important roles, namely as an entity and the identity of the Indonesian nation. The meaning of Pancasila as an entity is something that has a unique and different existence, although not necessarily in physical form. In this case, Pancasila as an entity of the Indonesian nation has its own characteristics, namely the diversity of values ​​contained in it (Sari, S. A. T., et al, 2023). Diversity in terms of culture, language, ethnicity, race, ethnicity, beliefs, traditions and socialization processes which are a reflection of the Indonesian nation is the meaning of Pancasila as the nation's identity. This identity also indicates the existence of a characteristic that is different from other nations because the entire community always reflects on the values ​​or guidelines contained in Pancasila. Pancasila as the entity and identity of the Indonesian nation needs to be known, understood and preserved by every Indonesian citizen (Dwiputri, F. A., & Anggraeni, D, 2021).